PENGARUH PERTUMBUHAN EKONOMI DAN KEMISKINAN TERHADAP IPM 14 KABUPATEN KATEGORI “SEDANG” DI PROVINSI JAWA TIMUR - Mayang Dwi Pitaloka; P.S Prabowo (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
This study aims to see the significant influence of Economic Growth and Poverty on the Human Development Index (HDI) of 14 districts with the "Medium" category in East Java Province. The analytical method used is panel data regression, the data used is data for the period 2016-2020 in 14 districts in East Java Province. The technique for collecting data in this research is to use the documentation method sourced from the Central Statistics Agency to obtain information related to the Human Development Index (HDI), Gross Regional Domestic Product (GRDP), and Poverty Rates. The results of the calculations on panel data regression show that economic growth and poverty have a negative influence and simultaneously the variables of economic growth and poverty have a significant influence on the HDI of 14 districts in East Java Province for the 2016-2020 period.Key Words: SFA, Panel Data, Efficiency